Mengukur Loyalitas Pelanggan Berdasarkan Pemasaran Relasional dan Kebijakan Harga Pada Bidang Usaha Retail Berbasis B2B di Kota Tasikmalaya - Ari Arisman; Depy Muhamad Pauzy (JURNAL EKONOMI PERJUANGAN, 2019)
The purpose of this study is to find the effect of relational marketing and pricing policies on customer loyalty in the B2B-based retail business in the City of Tasikmalaya. This research is descriptive and empirical. Descriptive research was conducted to obtain an overview of the attributes of online stores, consumer satisfaction and trust. While empirical research is conducted to determine the relationship between variables through statistical calculations. The technique of collecting data through questionnaires to 100 respondents who were consumers of sandal craft material stores based on Business to Business (B2B) using judgment sampling or purposive sampling techniques. As well as the analytical tool used in this study is path analysis (path analysis) where the attributes of relational marketing and price policies become exogenous variables and customer loyalty becomes variable. The results of this study indicate that relational marketing and pricing policies have an important role in creating customer loyalty. The better relational marketing and pricing policies, the more customer loyalty will increase.